OBESITY AS A COMMON COMORBIDITY IN PATIENTS WITH DIABETES: OCCURRENCE BASED ON EATING HABITS AND OTHER DETERMINANTS IN WEST JAVA, INDONESIA - SUHARTATIK, MELIZA; DEWI SARTIKA, RATU AYU (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The prevalence of obesity in individuals with diabetes mellitus (DM) is fairly high. It has been shown that obesity worsens insulin resistance and can elevate the risk for complications of diabetes. Therefore, this study aimed to assess the prevalence of obesity and to determine the factors that affect obesity in adults with DM. Methods: This study used a cross-sectional design and included secondary data from the “Cohort Study of Risk Factors for Non-communicable Diseases.” The study was conducted on adults with DM at Kebon Kelapa Village, West Java, in 2017, and the total sample obtained for analysis was 112 respondents. Results: In this study, 62.5% of adults with DM were overweight or obese (body mass index ≥25 kg/m2). Factors found to influence the incidence of obesity in adults with DM were sex and macronutrient intakes, namely, “over” energy intake, “over” carbohydrate intake, “over” fat intake, and “normal” protein intake. Risk of obesity was 3.15-fold higher in female than male participants with diabetes. The highest risk for increased obesity level in adults with diabetes was found in those with “over” fat intake (odds ratio, 8.33). Conclusions: In adults with diabetes, the incidence of obesity is a trigger of complications. Therefore, to improve the quality of life of individuals with diabetes, attention must be given to managing their weight.